Expanding Accessibility: Sensory Sensitive Programming for Museums. (18th November 2021) - Schwartzman, Rachel; Knowles, Christen
Abstract: Museums in the US have a responsibility to provide accessible facilities stipulated by the American with Disabilities Act (ADA). Unfortunately, programming adjustments beyond physical accessibility is generally an emerging consideration or only implemented in large, established institutions. Although some museums have implemented disability‐specific programming, focusing on more universal challenges of access (e.g., sensory needs) can increase accessibility in a museum of any size and budget. The following manuscript presents an example of a small science museum in a mid‐size city and the development and implementation process of innovative sensory‐sensitive programming for community members with disabilities and their families. By addressing a common characteristic that spans across different disabilities, the Sensory Sensitive Program (SSP) was successfully implemented and attended by a diverse array of community members. Feedback from patrons attending the pilot event is reported and used to inform the iterative development process for the program. Considerations for future implementation of SSP are provided.